Meaningful Futures with Robot Designing a New Coexistence - Dörrenbächer, Judith; Ringfort-Felner, Ronda; Neuhaus, Robin; Hassenzahl, Marc (Chapman & Hall/CRC Artificial Intelligence and Robotics Series, 2023)
a, aI, Coexistence, Designing, Dorrenbacher, Dörrenbächer, et, Felner, Futures, Hassenzahl, Judith, Marc, Meaningful, Neuhaus, New, Ringfort, Robin, Robots, Ronda